The Agreement Between Current Stone Analysis Techniques and SEM-EDAX in Urolithiasis - Taheri, Maryam; Basiri, Abbas; Taheri, Fatemeh; Khoshdel, Ali Reza; Fallah, Mohammad Ali; Pur nourbakhsh, Faranak (Urology Journal, 2019)
Purpose: Nowadays, there are many physical and chemical methods available for urinary stone analysis. According to the latest guidelines, infrared spectroscopy (IR) or x-ray diffraction (XRD) are the two preferred methods in this issue. Therefore, we decided to do a practical comparison between the two above-mentioned techniques with a reference method in order to set up a proper analysis method in our clinical laboratories. Materials and Methods: A total of 60 kidney stones were obtained at Labbafinejad hospital through open surgery or percutaneous nephrolithotomy. Then stone analysis techniques included both a morphological examination by SEM (Scanning Electron Microscopy) and internal structure analysis by EDAX (Elemental distribution analysis X-ray), XRD, IR and wet chemical analysis. SEM together with EDAX (SEM-EDAX) was considered as reference methods. Results: The results of XRD had the highest agreement with SEM-EDAX analysis (93%), while the total agreement of FTIR and wet chemical analysis was 81% and 71% respectively. The agreement of FTIR for calcium oxalate stones was acceptable (90%), but for uric acid and cystine stones was challenging (65% and 76% respectively). Conclusion: Our results revealed that XRD is more reliable than FTIR; but considering cost issues, FTIR is more suitable for routine clinical laboratory. Moreover, wet chemical analysis, which is routinely used in our laboratories is insufficient for stone analysis and it is mandatory to be replaced by techniques that are more accurate.